The flying trunk and other stories from Hans Andersen - Lewis, Naomi (Prentice-Hall Books for Young Readers, 1986)
Retells thirteen fairy tales by the Danish author, including "The Tinderbox," "The Steadfast Tin Soldier," "The Little Match Girl," and "The Snowman."